First step in the assessment of mechanical properties of pure API: production of tablet with minimum addition of excipient - Naz Hasan Huda, Yeakuty Marzan Jhanker, Riaz Uddin (Journal of Applied Pharmaceutical Science)
There are a number of challenges during tablet dosage form development like excipient selection, poor powder flow, poor tableting, lack of hardness, high friability, elevated disintegration time, low dissolution rate etc. Most of them are significantly influenced by the mechanical properties (like elasticity, plasticity, brittleness, powder compressibility, tensile strength, etc.) of the active pharmaceutical ingredient (API). Assessment of these properties of the pure actives is not always easy. Absence of lubrication may induce a lot of friction, causing capping, lamination or sticking or in many cases, combination of them, damaging the test tablet when taken out. Different approaches were studied to overcome this problem and a solution was found by compaction of a tablet of Sodium Starch Glycolate-Magnesium Stearate in a ratio of 2.75:1 before compressing each tablet of pure API.
Keywords: Active pharmaceutical ingredient, Magnesium Stearate, Lubrication, Sodium Starch Glycolate.